2022
DOI: 10.1017/s003329172200321x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced magnetic mismatch negativity: a shared deficit in psychosis and related risk

Abstract: Background Abnormal auditory processing of deviant stimuli, as reflected by mismatch negativity (MMN), is often reported in schizophrenia (SCZ). At present, it is still under debate whether this dysfunctional response is specific to the full-blown SCZ diagnosis or rather a marker of psychosis in general. The present study tested MMN in patients with SCZ, bipolar disorder (BD), first episode of psychosis (FEP), and in people at clinical high risk for psychosis (CHR). Methods Source-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
2
1
Order By: Relevance
“…Despite the causes behind the exacerbated left vs. right structural abnormalities in SZ are outside the scope of the present study, we speculate that the different cytoarchitectonic organization of left and right auditory cortex (Harrison et al, 2010) may result in a differential sensitivity to the underlying pathophysiology and link with language‐related symptoms such as auditory hallucinations and impaired verbal cognition (Heidrich & Strik, 1997). On the other hand, our results contrast with the few other EEG dipole‐fitting (Oades et al, 2006; Randau et al, 2019) and MEG source‐localization (Valt et al, 2022) studies in FE that found right (Randau et al, 2019) or bilateral dMMN reductions, suggesting further research is necessary to account for the variability of the source‐reconstruction techniques applied in different studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Despite the causes behind the exacerbated left vs. right structural abnormalities in SZ are outside the scope of the present study, we speculate that the different cytoarchitectonic organization of left and right auditory cortex (Harrison et al, 2010) may result in a differential sensitivity to the underlying pathophysiology and link with language‐related symptoms such as auditory hallucinations and impaired verbal cognition (Heidrich & Strik, 1997). On the other hand, our results contrast with the few other EEG dipole‐fitting (Oades et al, 2006; Randau et al, 2019) and MEG source‐localization (Valt et al, 2022) studies in FE that found right (Randau et al, 2019) or bilateral dMMN reductions, suggesting further research is necessary to account for the variability of the source‐reconstruction techniques applied in different studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Smaller grey matter volumes in HG of SZ but not BD were also found by Kasai et al (2003). Conversely, other studies comparing FE sz and affective‐spectrum disorder have found similar MMN reductions (Kaur et al, 2011; Valt et al, 2022). Future studies tracking MMN deficits in FE sz and FE Aff longitudinally and with larger samples should resolve the specificity of the deficit.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation